Landslides, a Key Landform in the Global Geological Heritage - Morino, Costanza; Coratza, Paola; Soldati, Mauro (Frontiers in Earth Science, 2022)
Landslides are important components of global geoheritage, but awareness of their significance and value in such terms seems scanty in the scientific community. Landslides are normally identified among various features of geological and geomorphological interest, and often considered a source of hazard. However, they are seldom identified as geosites and as part of geoheritage. This paper aims at filling these gaps by highlighting the importance of landslides in the global geoheritage. After a short introduction on the values and criteria to define landforms as geosites, based on literature review, we show to what extent landslides have been defined as geomorphosites and as part of geoheritage around the world. We then outline three aspects that should be specifically considered in the identification of landslides as geomorphosites, namely (i) past and present climate changes, (ii) anthropic signature, and (iii) risk perception. Finally, we describe four cases of spectacular landslides that serve as significant examples worldwide.